2022
DOI: 10.1155/2022/7502294
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Unknown Threat Based on Continuous-Time Dynamic Heterogeneous Graph Network

Abstract: Unknown threats have caused severe damage in critical infrastructures. To solve this issue, the graph-based methods have been proposed because of their ability for learning complex interaction patterns of network entities with discrete graph snapshots. However, such methods are challenged by the computer networking model characterized by the natural continuous-time dynamic heterogeneous graph (CDHG). In this paper, we propose a CDHG-based graph neural network model, namely, CDHGN, for unknown threat detection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Literature [16] envisioned a deep learning model developed to address network traffic security for various IoTs to solve network security problems; testing the above model on an open dataset showed that the model achieved 99% accuracy in identifying potential threats. Literature [17] conceptualized a cdhg-based graph neural network model for the detection of unknown threats to the network, and tests were conducted on a comprehensive network security dataset of 9 million+ data records, which corroborated the reliability and excellent performance of this method. Literature [18] proposed a Deep Embedded Neural Network Expert System (DeNNeS), which refines rules through deep autonomous learning and classifies them based on its knowledge base.…”
Section: Introductionmentioning
confidence: 82%
“…Literature [16] envisioned a deep learning model developed to address network traffic security for various IoTs to solve network security problems; testing the above model on an open dataset showed that the model achieved 99% accuracy in identifying potential threats. Literature [17] conceptualized a cdhg-based graph neural network model for the detection of unknown threats to the network, and tests were conducted on a comprehensive network security dataset of 9 million+ data records, which corroborated the reliability and excellent performance of this method. Literature [18] proposed a Deep Embedded Neural Network Expert System (DeNNeS), which refines rules through deep autonomous learning and classifies them based on its knowledge base.…”
Section: Introductionmentioning
confidence: 82%